Development of Stress in 1st-year Medical Students and Its Relationship with Cognition and Telomere Length: A Prospective Pilot Study - Parul Horo; Farah Khaliq; Neelam Vaney; Rajarshi Kar (Annals of African Medicine, 2026)
Abstract Background: First-year medical students experience stress as they are exposed to an entirely new environment with a vast academic course. Aims: The present study was planned to explore the development of stress during the 1 st year in medical students and to correlate the level of stress with cognition and telomere length. Methodology: This prospective study was conducted on 30 1 st -year medical students. The level of stress was assessed by the Medical Student Stressor Questionnaire (MSSQ). Event-related potentials were used as an indicator of cognitive functions. Telomere length assessment was done by the quantitative polymerase chain reaction method. The readings were taken at the beginning of the session and at the end of their 1 st year. Results: The level of stress increased in all six domains significantly at the end of the 1 st year in medical students. The mean of academic-related stress (ARS) scores at the start of the session was 1.52 ± 0.32, and at the end of their 1 st year, it increased to 2.23 ± 0.51 depicting that the ARS was the major cause of stress in students. There was a decrease in P300 latency from 238.11 ± 24.49 to 222.82 ± 33.19 depicting an improvement in cognitive function. Telomere length decreased with an average telomere attrition of 325 ± 100.27 base pairs to 302.59 ± 91.31 base pairs over the year, but it did not reach the significant value. Conclusions: The level of stress increased during the 1 st year in medical students. Mild stress seems to be beneficial and improved cognition in 1 st -year medical students. The shortening of telomere length over the year observed in our study did not reach the significant value. No correlation of stress scores with telomere length and cognition was observed. Studies with larger sample size and duration are suggested.